Polyphenols as Natural Antioxidants in Skin Aging - Yenny, Satya Wydya; Suryani, Yulia Eka (Sumatera Medical Journal, 2020)
Skin aging is a complex biological process influenced by a combination of intrinsic and extrinsic factors, leading to cumulative alterations of skin struture, function and appearance. Polyphenols represent a superfamily of diverse naturally occurring phytochemicals. Current research reveals that phenolic compounds in plants possess high antioxidant activity and free radical scavenging capacity and can prevent the body from oxidative damage over human life span. This review focuses on present understanding of skin aging and the effects of polyphenols in the context of anti-agieng activity.